THE EFFECT OF PROFITABILITY AND LIQUIDITY ON THE TIMELINESS OF FINANCIAL REPORTING - Euis Ratnasari; Nurahmelia Putri; Soedjatmoko Soedjatmoko (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to analyze the influence of profitability and liquidity on the timeliness of financial reporting in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2021-2023 period. Profitability is measured using the return on assets (ROA) ratio, while liquidity is measured by the current ratio. This study is a quantitative study, the number of company samples is 30 samples from 10 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for a period of 3 years, namely 2021-2023. This study uses secondary data obtained through the company's annual report. Data analysis uses logistic regression tests, several tests, namely, descriptive statistics, classical assumption tests (multicollinearity test), logistic regression analysis of regression model feasibility (geometry of fit), testing the whole model (overall model fit), classification matrix and hypothesis test (determination coefficient test (Nagelkerke R square), T test (partial test) and F test (simultaneous test). The results of the data analysis show that partially and simultaneously the profitability and liquidity variables have no effect on the timeliness of financial reporting in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2021-2023 period.